Lichen sclerosus following genital piercing. (April 2022) - Chan, S; Watchorn, RE; Muneer, A; Bunker, CB
Male genital lichen sclerosus (MGLSc) is a chronic inflammatory dermatosis that predominantly affects uncircumcised males. Several aetiological factors have been described, with growing evidence supporting chronic urine exposure of susceptible epithelium being crucial to its pathogenesis. We describe a 45-year-old man with a 2-year history of MGLSc at the site of a urethrocutaneous fistula secondary to a penile piercing. To our knowledge, this is the first documented case of MGLSc occurring at the site of a genital piercing.